Technical Perspective A Breakthrough in Software Obfuscation. - Barak, Boaz (Communications of the ACM, 2016)
The author offers a technical perspective on the breakthrough in software obfuscation. He discusses the rise of cryptographic concepts and applications including public key cryptography, secure function evaluation, and zero knowledge proofs. He comments on the feasibility of the natural notion of virtual black box obfuscation with reference to a research paper in which cryptographic multilinear maps were constructed.